Hearing preservation and clinical outcome of 32 consecutive electric acoustic stimulation (EAS) surgeries. (July 2014) - Usami, Shin-Ichi; Moteki, Hideaki; Tsukada, Keita; Miyagawa, Maiko; Nishio, Shin-Ya; Takumi, Yutaka; Iwasaki, Satoshi; Kumakawa, Kozo; Naito, Yasushi; Takahashi, Haruo; Kanda, Yukihiko; Tono, Tetsuya
Abstract Conclusions: Our results indicated that electric acoustic stimulation (EAS) is beneficial for Japanese-speaking patients, including those with less residual hearing at lower frequencies. Comparable outcomes for the patients with less residual hearing indicated that current audiological criteria for EAS could be expanded. Successful hearing preservation results, together with the progressive nature of loss of residual hearing in these patients, mean that minimally invasive full insertion of medium/long electrodes in cochlear implantation (CI) surgery is a desirable solution. The minimally invasive concepts that have been obtained through EAS surgery are, in fact, crucial for all CI patients. Objectives: This study was conducted to evaluate hearing preservation results and speech discrimination outcomes of hearing preservation surgeries using medium/long electrodes. Methods: A total of 32 consecutive minimally invasive hearing preservation CIs (using a round window approach with deep insertion of a flexible electrode) were performed in 30 Japanese patients (two were bilateral cases), including patients with less residual hearing. Hearing preservation rates as well as speech discrimination/perception scores were investigated on a multicenter basis. Results: Postoperative evaluation after full insertion of the flexible electrodes (24 mm, 31.5 mm) showed that residual hearing was well preserved in all 32 ears. In all patients, speech discrimination and perception scores were improved postoperatively.